Data-Based Education Service Quality Improvement Management in the Digital Era - Abdurrahman, Abdurrahman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research examines the role of strategic management, program evaluation, and educational planning in formulating a relevant educational vision in the digital era and improving the quality of educational services through data-driven decision-making. The method used is a bibliographic study by searching the literature through leading academic databases, using keywords such as strategic management, educational program evaluation, and data-driven decision making. The selected literature meets the criteria of scientific quality and up-to-dateness, primarily focusing on publications of the last five years. The relevant literature is then analyzed thematically to identify key concepts, underlying theories, and findings that can be adopted in Indonesia's education context. The study results show that Indonesia's education sector faces various strategic challenges, including education planning that has not fully considered technological dynamics and labor market demands. This research emphasizes the importance of implementing adaptive strategic management, participatory program evaluation, and data-driven planning to formulate a contextual educational vision in the digital era. These three approaches are crucial in improving the quality of inclusive, relevant, and sustainable education services in Indonesia. Further research can be conducted field studies to test the effectiveness of implementing data-based management in certain educational units.